Contact Analysis of Cylindrical Helical Gear Considering the Hob Installation Error - Zhang Rui; Wu Zhifei; Wang Tie; Yan Tianxiao; Wu Pingan; Qiao Jinwei (Jixie chuandong)
The high precision gear processing must consider the influence of machining error on the meshing quality,based on the basic principle of the contact analysis of helical gear,the simulation of involute helical gear is realized by using the Matlab software,then tooth contact trace and the transmission error cure is obtained. By comparing the gear transmission error curve under different hob installation error,the sensitivity of the transmission error on different hob installation error is analyzed. The gear mesh quality will be connected with the hob installation error by the research methods of this article,which will provide the basis for subsequent finishing.